Characterization of Clinically Relevant Strains of Extended-Spectrum β-Lactamase-Producing Klebsiella pneumoniae Occurring in Environmental Sources in a Rural Area of China by Using Whole-Genome Sequencing - Chi, Xiaohui; Berglund, Björn; Zou, Huiyun; Zheng, Beiwen; Börjesson, Stefan; Ji, Xiang; Ottoson, Jakob; Lundborg, Cecilia Stålsby; Li, Xuewen; Nilsson, Lennart E. (Frontiers in Microbiology, 2019)
Abstract Klebsiella pneumoniae is a gram-negative, opportunistic pathogen and a common cause of healthcare-associated infections such as pneumonia, septicemia and urinary tract infection. The purpose of this study was to survey the occurrence of and characterize K. pneumoniae in different environmental sources in a rural area of Shandong province, China. 231 samples from different environmental sources in 12 villages were screened for extended-spectrum β-lactamase-(ESBL)-producing K. pneumoniae, and 14 (6%) samples were positive. All isolates were multidrug-resistant and a few of them belonged to clinically relevant strains which are known to cause hospital outbreaks worldwide. Serotypes, virulence genes, serum survival and phagocytosis survival were analyzed and the results showed the presence of virulence factors associated with highly virulent clones and a high degree of phagocytosis survivability, indicating the potential virulence of these isolates. These results emphasize the need for further studies designed to elucidate the role of the environment in transmission and dissemination of ESBL-producing K. pneumoniae and the potential risk posed to human and environmental health. Key words: ESBL, Klebsiella pneumoniae, Environment, Feces, Water, Soil, Vegetable, Sediment, MLST, PFGE, Whole-genome sequencing